Photoluminescence studies of the 640nm center in electron irradiated IIa diamond. Issue 8 (13th September 2020) - Zhang, Yufei; Wang, Kaiyue; Chang, Sen; Tian, Yuming; Li, Junlin
Abstract: In this study, a 640 nm center was observed in electron-irradiated type IIa diamond by low-temperature photoluminescence spectroscopy. The origin of the center was explored by temperature dependence analysis. The optical center was at 639.6 nm and adjacent to the negative nitrogen-vacancy center. According to the calculation of energy difference, the splitting of excited states of the nitrogen-vacancy center was excluded as the origin of the 640 nm center. The lattice contraction and electron-phonon coupling model was employed to fit the temperature dependence of the 640 nm center, with all results indicating that the optical center was interstitial defect-related.